1998
DOI: 10.1021/np970507w
|View full text |Cite
|
Sign up to set email alerts
|

Macrocyclic Diterpenoids from Euphorbia semiperfoliata

Abstract: In addition to known compounds, the aerial parts of E. semiperfoliata afforded an abietanolide (3), 13 jatrophane polyesters (4-9, 12, 14-19), two 4-deoxyphorbol diesters (23, 24), and a pair of epimeric diterpenes (21, 22) with a novel carbon skeleton, which was named euphoperfoliane. Structures were determined by spectroscopic analysis, and the main conformational features of jatropha-6(17),11-dienes are discussed in detail. The obtained isolation yield of several jatrophanes was unprecedented within the spu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 18 publications
4
86
0
1
Order By: Relevance
“…Assuming the S configuration at C-4, typical of all the members of the jatrophane family isolated to date (deduced by X-ray analysis of some derivatives) (Hohmann et al 1997), the absolute stereochemistry reported in structure 1 could be confidently assigned to euphodendroidin A. Moreover, it should be noted that the small value of J H-4/H-5 (1.2 Hz) has been correlated with a conformation of the 12-membered ring with the exomethylene group pointing outward and H-5 pointing inward (Appendino et al 1998). Accordingly, H-5 showed ROESY cross-peak with both OH-15 and with H-12.…”
Section: Jatrophane Diterpenes: Euphorbia Dendroidesmentioning
confidence: 82%
See 1 more Smart Citation
“…Assuming the S configuration at C-4, typical of all the members of the jatrophane family isolated to date (deduced by X-ray analysis of some derivatives) (Hohmann et al 1997), the absolute stereochemistry reported in structure 1 could be confidently assigned to euphodendroidin A. Moreover, it should be noted that the small value of J H-4/H-5 (1.2 Hz) has been correlated with a conformation of the 12-membered ring with the exomethylene group pointing outward and H-5 pointing inward (Appendino et al 1998). Accordingly, H-5 showed ROESY cross-peak with both OH-15 and with H-12.…”
Section: Jatrophane Diterpenes: Euphorbia Dendroidesmentioning
confidence: 82%
“…ROESY spectra determined the location of a acetate and a isobutyrate at C-2 and C-6, respectively. The relative configuration of terracinolide J (11) was investigated by measurement of scalar and dipolar couplings as well as by comparison with literature data (Appendino et al 1998;Marco et al 1996Marco et al , 1997, and has been found identical to that of all known terracinolides isolated to date.…”
Section: Modified Jatrophane Diterpenes: Euphorbia Dendroidesmentioning
confidence: 84%
“…A jatrophane diterpene SJ23B (81, Figure 10) isolated from Euphorbia semiperfoliata [253] has shown a potential PKCα-mediated antiviral effect on HIV-1 infection and activation of latent HIV-1 gene expression, being 10-fold more potent than prostratin (70) [254].…”
Section: Other C1 Domain Ligandsmentioning
confidence: 99%
“…It is necessary to correct wrong configuration, also to clarify the interesting change of conformation in these types of diterpenes. 20 In Chinese traditional medicine XUSUIZI (Euphorbia lathyris), the main constituents are the lathyrane-type diterpenes, almost accounting for 5%, but the biological activities of macrocyclic lathyrane polyesters from E. lathyris have not been evaluated in depth before. 21,22 In our previous reports, configuration of several diterpenes have been investigated and rectified by X-ray diffraction.…”
Section: Introductionmentioning
confidence: 99%